Antibiotic prophylaxis in otolaryngologic surgery - Ottoline,Ana Carolina Xavier (2013)
AIM: Antibiotic prophylaxis aims to prevent infection of surgical sites before contamination or infection occurs. Prolonged antibiotic prophylaxis does not enhance the prevention of surgical infection and is associated with higher rates of antibiotic-resistant microorganisms. This review of the literature concerning antibiotic prophylaxis, with an emphasis on otolaryngologic surgery, aims to develop a guide for the use of antibiotic prophylaxis in otolaryngologic surgery in order to reduce the numbers of complications stemming from the indiscriminate use of antibiotics.